2021
DOI: 10.1021/acssuschemeng.1c07162
|View full text |Cite
|
Sign up to set email alerts
|

Solar Photocatalytic Oxidation of Methane to Methanol with Water over RuOx/ZnO/CeO2 Nanorods

Abstract: Due to the high stability and chemical inertia of methane, CH 4 , its selective conversion into value-added organic chemicals under mild conditions has been widely regarded as an important reaction for the chemical industry. Here, we develop a RuO x decorated ZnO/CeO 2 photocatalyst for the highly efficient and selective transformation of CH 4 into CH 3 OH under simulated solar light irradiation. The CH 3 OH generation rate over the optimized RuO x /ZnO/CeO 2 composite is 133.54 μmol g −1 h −1 with 97.7% selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…4a). 27–31 The opposite outcome was also reported, i.e. , mobile ˙OH stimulates the formation of C 2 H 6 , whereas the reaction of surface-bound ˙OH with CH 3 ˙ selectively produces methanol (Fig.…”
Section: Mechanistic View For Methane Conversion To Desired Productsmentioning
confidence: 90%
See 1 more Smart Citation
“…4a). 27–31 The opposite outcome was also reported, i.e. , mobile ˙OH stimulates the formation of C 2 H 6 , whereas the reaction of surface-bound ˙OH with CH 3 ˙ selectively produces methanol (Fig.…”
Section: Mechanistic View For Methane Conversion To Desired Productsmentioning
confidence: 90%
“…Reproduced with permission. 31 Copyright 2022, American Chemical Society. (b) Change of the reaction pathway for CH 4 oxidation before and after the surface fluorination of WO 3 .…”
Section: Mechanistic View For Methane Conversion To Desired Productsmentioning
confidence: 99%
“…41,42 Fortunately, transition metal oxides have been considered as one of the best candidates for effectively extracting holes and constructing hole transport channels. [43][44][45][46] Among them, CoO x has attracted the interest of many researchers in practical application on account of its high efficiency, affordable cost, and earth abundance. Li et al demonstrated that the CoO x cocatalyst could effectively capture holes in a few picoseconds and dramatically prolong the lifetime of photogenerated holes.…”
Section: Introductionmentioning
confidence: 99%
“…28 This not only greatly increases the number of active centers, but also results in improved photocatalytic performance via synergistic effects. 31,32 As compared to oxygen and N 2 O, H 2 O 2 oxidants are much more effective to catalyze CH 4 under mild conditions via generating hydroperoxy intermediate products. 10 However, for H 2 O 2 based CH 4 conversion, the effective utilization of H 2 O 2 to reduce cost is the main bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…28 This not only greatly increases the number of active centers, but also results in improved photocatalytic performance via synergistic effects. 31,32…”
Section: Introductionmentioning
confidence: 99%